PENGARUH KEMAMPUAN KERJA, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI YAYASAN RASTITI BHAKTI (EDUCATION ROCKS) - Ni Wayan Dela Laraswati; I Gst Ngurah Bagus Gunadi; Agus Wahyudi Salasa Gama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Every company really needs qualified human resources to achieve the company goals that have been determined. This study aims to determine the effect of work ability, work discipline and motivation on employee performance at the Rastiti Bhakti Foundation. This research was conducted at the Rastiti Bhakti Foundation with a total sample of 35 employees. The method of determining the sample of this research is saturated sampling method. Data collection was carried out through documentation, interviews and questionnaires. The data analysis technique used in this study was multiple linear regression analysis through the SPSS version 25 program. Based on the results of the analysis, this study shows that work ability has a positive and significant effect on employee performance at the Rastiti Bhakti Foundation, this means that the more employees work ability increases, the employee performance at the Rastiti Bhakti Foundation will also increase. Work discipline has a positive and significant effect on employee performance at the Rastiti Bhakti Foundation, this means that the more employee work discipline increases, the employee performance at the Rastiti Bhakti Foundation will also increase. Motivation has a positive and significant effect on employee performance at the Rastiti Bhakti Foundation, this means that the better the motivation given to employees, the employee performance at the Rastiti Bhakti Foundation will also increase.